2011
DOI: 10.1097/rlu.0b013e31821a2778
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG PET/CT Findings of Huge Cholesterol Granuloma in Multiple Ribs

Abstract: Cholesterol granuloma (CG) is a foreign body-type granuloma formed in reaction to cholesterol crystals. CG usually develops in pneumatized bones because of inadequate drainage, especially in the middle ear cavity. We report a case of a patient with huge CG involving multiple ribs. A 66-year-old man presented with chest discomfort of 8 months' duration. The chest radiograph showed a huge mass with rib destruction in the right upper lung, suggesting a malignancy. F-18 FDG PET/CT scan demonstrated large mass invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Both RFA and TACE m onotherapies beneficially affect survival and have been established as valuable treatment modalities for patients with unresectable HCC. Recent studies have suggested that RFA + TACE combination therapy could be expanded to patients with resectable HCC and transplant candidates [ 26 , 27 ]. According to BCLC staging and treatment algorithm, RFA is considered curative for early-stage HCC, and may be comparable to surgical resection in terms of OS and recurrence [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both RFA and TACE m onotherapies beneficially affect survival and have been established as valuable treatment modalities for patients with unresectable HCC. Recent studies have suggested that RFA + TACE combination therapy could be expanded to patients with resectable HCC and transplant candidates [ 26 , 27 ]. According to BCLC staging and treatment algorithm, RFA is considered curative for early-stage HCC, and may be comparable to surgical resection in terms of OS and recurrence [ 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Although rare, it can affect any region of the body. [3][4][5][6] Obvious fibrosis may be the pathological basis of high 68 Ga-FAPI-04 uptake in xanthogranulomatous cholecystitis. Meanwhile, an increasing number of case studies have reported 68 Ga-FAPI-04 uptake in various nonmalignant etiologies, including myocardial infarction, 7 immunoglobulin G4-related disease, [8] tuberculosis, 9 shoulder arthritis, 10 pancreatitis, 11 and fibromas.…”
mentioning
confidence: 99%
“…Xanthogranulomatous cholecystitis is a rare variant of chronic cholecystitis characterized by lipid-laden macrophages causing xanthogranulomas, foam cells, and severe fibrosis 2 . Although rare, it can affect any region of the body 3–6 . Obvious fibrosis may be the pathological basis of high 68 Ga-FAPI-04 uptake in xanthogranulomatous cholecystitis.…”
mentioning
confidence: 99%
“…Cholesterol granulomas are frequently described occurring in the temporal bone as a result of inflammatory ear disease. 1 However, they are not exclusive to this location. An intraventricular cholesterol granuloma near the septum pellucidum thought to be secondary to remote head trauma from a motor vehicle collision was previously reported.…”
Section: Discussionmentioning
confidence: 92%